STUDY TO ASSESS AWARENESS ABOUT HIV/AIDS AMONG MEDICAL STUDENTS: Life Science-Internal Medicine - ELSAYED ABOZEID, HANAA; ABDULRAHMAN ALGHOFAILI, NOUF; ABDULRAHMAN BAOTHMAN, ROTAN; NASER ALMOTAIRI, KHAWATER; ADEL TURKSTANI, GHAIDA; SALEM ALJEZANI, KHOLOUD (International Journal of Life Science and Pharma Research, 2019)
The acquired immunodeficiency syndrome (AIDS) is a fatal illness caused by a retrovirus known as the Human Immunodeficiency Virus (HIV) which breaks down the body's immune system. Lack of awareness and misconceptions about HIV/AIDS in the general population is responsible for rapid spread and social stigma. This study aimed to assess knowledge and attitudes about HIV/AIDS among medical students in Jeddah, Saudi Arabia. An observational cross-sectional study was performed on 400 participants selected randomly from the medical students at IbnSina National College. The assessment was carried out by obtaining a self-administered, structured questionnaire about knowledge and attitude of students about HIV/AIDS. Questionnaire obtained from Biradar et al., 2016 and included 13 items. The study sample included 108 male and 292 female and more than one third (36.3%) of the students in the sixth academic year. All students were conscious about HIV/AIDS disease and all of them except one had information about the causative agent (virus). The majority (70.3%) of students had gained information from doctors/health worker followed by other sources like media. More than half of them were aware of about the modes of transmission and preventive approaches. The results of the present study are encouraging as most of the students had good awareness regarding HIV/AIDS disease. Role of doctors/health worker and media are very important to spread the awareness among the general population. These measures will help to reduce the misconception and indifferent attitude towards the HIV infected patients.